Effects of carbohydrates and electrolytes on thermoregulatory responses and anaerobic performance following a prolonged exercise in the heat - Silami-Garcia, Emerson; Rodrigues, Luiz Oswaldo Carneiro; Faria, Marcelo Henrique Salviano de; Araújo-Ferreira, Ana Paula; Nassif-Leonel, Camila; Stradioto, Mayra Alves; Cançado, Gustavo Henrique da Cunha Peixoto; Oliveira, Mônica Cristina de; Sakurai, Emília (Brazilian journal of physical education and sport, 2004)
Most of the energy needed for muscle contraction during the Wingate anaerobic test is derived from adenosine triphosphate, creatine phosphate and glucose breakdown. Exogenous carbohydrates contribute to the maintenance of blood glucose and that could lead to the improvement of anaerobic performance following a prolonged sub-maximal exercise (PE). The purpose of the present study was to compare the anaerobic power output of men in the Wingate test performed immediately after 90 min of cycling at 60% of the maximal workload, with and without the ingestion of carbohydrates and electrolytes (CHO), as well as the physiological responses during the PE. Seven men (21.4 ± 4.2 yrs; 65.46 ± 10.45 kg; 9.4 ± 1.8% fat and 60.38 ± 4.76 mLO2.kg-1.min-1) volunteered for the study. They received adequate amounts of distilled water and capsules containing either glucose and electrolytes (CHO) or placebo (PLA) at every 15 min, while exercising on an environmental chamber at 28 ºC temperature and 79% air relative humidity, in a double-blind protocol. Rectal temperatures and heart rates were monitored continuously. Blood glucose and lactate were also measured. Sweat rates were estimated from pre to post-exercise body weight differences, taking into account water intake and urine excretion. As expected, blood glucose was significantly higher (p ≤ 0.05) in CHO (116 ± 12mg/dL) than in PLA (81 ± 7mg/dL). Relative power output in CHO (12.63 ± 1.27 W·Kg-1) and in PLA ( 12.64 ± 1.30 W·Kg-1) as well as the total work output in CHO (18.57 ± 2.86 KJ) and in PLA (20.36 ± 6.01 KJ) were not different. Thermal regulation was also unaffected. The ingestion of CHO did not affect any of the variables under investigation